National Nursing Home Survey, 1977 ([Verlag nicht ermittelbar], 1984)
Data for the 1977 National Nursing Home Survey were collected in a nationwide sample of nursing homes, personal care homes (with or without nursing), and domicilary care homes. Information on staff, residents, and discharges was collected via a combination of personal interviews and self-enumerated forms. Four files are contained within this data collection. Part 1, Facility-Expense File, contains information on type of facility, certification, bed size, services and therapy routinely provided to residents or non-residents, regular and temporary admissions, vacant staff positions, facility income, and expenditures. Parts 2 and 3, Current and Discharged Resident Files, supply data on residents regarding admissions, impairments, conditions, behavioral problems, visits to a physician, services, therapy or treatments received, use of aids or need of assistance, level of care received, total charges for care, and sources and amount of payments. Part 4, Staff File, contains information on employees' job experience, services performed, hours worked, educational background, non-degree training, salaries, and benefits.